Initial discomfort and pain perception related with orthodontic aligners and fixed appliances: a systematic review - Védrenne, Céline Audrey Flore (2020)
Aims: To compare the initial discomfort between the two orthodontic methods, with pain measurements, control of the frequency of taking analgesics, and changes in daily routine. Materials and methods: The article searches were mainly carried out on the Pubmed and ResearchGate websites, using the following keywords: "invisalign", "fixed appliance", "pain", "analgesics", "discomfort", "impact on daily performance", in addition to an in-depth study of the bibliographies. Results: Eight studies were deemes relevant to our work. Conclusion: With a lower certainty, the pain in patients using aligners seems to be less intense than in patients with fixed applainces and the use of analgesic is therefore more important for the fixed group. These two parameters follow a gradual decrease during the first week of treatment. Chewing, speaking and general activity can be affected by the treatment.